1996
DOI: 10.1113/jphysiol.1996.sp021686
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐activated proton current in eosinophils from human blood.

Abstract: 1. The resting membrane potential of freshly purified normodense human eosinophils bathed in and dialysed with quasi-physiological solutions was -63 + 2 mV (n = 100). 2. In voltage-clamp mode with quasi-physiological internal and external solutions, voltage steps from the holding potential of -60 mV to levels positive to +20 mV resulted in development of a quasi-instantaneous outward current and a slowly developing outward current. The instantaneous current was absent when the cells were bathed in and dialysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
115
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 37 publications
3
115
0
Order By: Relevance
“…Although several groups have described the presence of proton channels in eosinophils (Gordienko et al, 1996;Schrenzel et al, 1996;Bánfi et al, 1999;Bankers-Fulbright et al, 2001;Cherny et al, 2001;DeCoursey et al, 2001a;DeCoursey et al, 2001b), the membrane potential determined by current clamp measurements indicated that depolarization following activation of NADPH oxidase was not sufficient to activate the proton channel (Gordienko et al, 1996;Tare et al, 1998;Bánfi et al, 1999). Eosinophil resting membrane potential has been reported to be between -60 and -80 mV (Gordienko et al, 1996;Tare et al, 1998). After activation of eosinophil NADPH oxidase with intracellular NADPH and GTPγS and after blocking the inwardly rectifying K + channel, Bánfi et al (Bánfi et al, 1999) reported a 40 mV depolarization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several groups have described the presence of proton channels in eosinophils (Gordienko et al, 1996;Schrenzel et al, 1996;Bánfi et al, 1999;Bankers-Fulbright et al, 2001;Cherny et al, 2001;DeCoursey et al, 2001a;DeCoursey et al, 2001b), the membrane potential determined by current clamp measurements indicated that depolarization following activation of NADPH oxidase was not sufficient to activate the proton channel (Gordienko et al, 1996;Tare et al, 1998;Bánfi et al, 1999). Eosinophil resting membrane potential has been reported to be between -60 and -80 mV (Gordienko et al, 1996;Tare et al, 1998). After activation of eosinophil NADPH oxidase with intracellular NADPH and GTPγS and after blocking the inwardly rectifying K + channel, Bánfi et al (Bánfi et al, 1999) reported a 40 mV depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic protons are generated directly by NADPH oxidation and indirectly by regeneration of NADPH via the hexose monophosphate shunt (Borregaard et al, 1984;Lukacs et al, 1993). Associated with NADPH oxidase is an outwardly rectifying proton channel that is functionally required for continued oxidase activity (Henderson et al, 1988;Gordienko et al, 1996;Schrenzel et al, 1996). This NADPH oxidaseassociated proton channel is ligand-and voltage-regulated and has a predicted reversal potential that is nearly equal to the equilibrium potential for protons (EH).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first patch clamp study on human granulocytes described nonselective cation channels activated by increased intracellular free calcium (3). Subsequently, the patch clamp technique has been used to explore proton, chloride, and potassium currents in neutrophils and eosinophils (4)(5)(6)(7)(8), as well as in many other nonexcitable cells.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been done with ~100 mM buffer, and concentrations as high as 200 mM buffer with no other cations have been used (14) (see Note 6). Table 1 shows examples of solutions that have been used to study H + channels (22,6,28). …”
mentioning
confidence: 99%